Pelatihan Mediator sebagai Strategi Penguatan Literasi Perkawinan bagi Penyuluh Agama - Eva, Yusnita; Isnaini, Isnaini; Wahyu Ningsih Baeha, Fajriah; Ramadhani, Yunisa; Darmawan, Aldy; Izzati, Nurul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Penyuluh Agama Islam (PAI) at the Kantor Urusan Agama (KUA) in Padang Pariaman Regency play a crucial role as the frontline in advocating for couples and resolving community conflicts. However, PAI has not yet functioned optimally, as reflected by the high divorce rate in this region, ranking second after Padang City in West Sumatra. Conflicting couples also tend to overlook the role of PAI and KUA as third parties that could help mediate their issues. To address this, the community service team sought to enhance PAI’s performance through ToT (Training of Trainers) mediator training, aimed at strengthening marital literacy and preserving marriages in the region. The approach used was group counseling with the Community-Based Rehabilitation (CBR) method. Data analysis applied Miles and Huberman’s techniques, including data reduction, data display, and conclusion drawing, alongside the Logical Framework Approach (LFA) for a more structured analysis. This training is beneficial in preparing PAI to become professional mediators, skilled in resolving household conflicts and reducing the tendency of couples to pursue litigation through the Pengadilan Agama (Religious Court).